Classroom discipline and control : 101 practical techniques - Chernow, Fred B., 1932-; Chernow, Carol (West Nyack, N.Y. : Parker, 1981)
Establishing control the very first day. Handling specific discipline infractions. Managing group discipline problems. Making yourself perfectly clear. Approaching homework as a factor of discipline....
Keywords: Education; Classroom management; Classroom management -- Handbooks, manuals, etc; School children -- Discipline